Nucleotide Sequence Analysis of the HN Gene of the Heat Resistant NDV Strain Af2240 and Substrain V4-UPM - Tan, Wen Siang (1994)
Newcastle disease virus (NOV) is the prototy peavian Paramyxovirus which causes a major disease in poultry. The highlyvi rulentv elogenic NDV strain AF 2240 andavi rulent substrainV4 - UPM possess thermost a blehaemag glutination andneura minidase activities compared to other strains. Therefore,the purpose of this study is to sequence the ha emagglutinin- neura minidase(HN)genes of AF 2240 and V4-UPM. The virus was propagated in the allantoic fluid of 9-10day-old embryonated eggs. The allantoic fluid was harvested after 72 hours incubation at 37°C. Viral purification was carried out on 30% to 60% (N/V ) sucrose density gradient centrifugation at 2 75,000 x g, for 4 hour sat 4°C. The viral RNA was extracted using the hot phenol extraction method. RNA sequencing was performed directly on the genomic RNA using the dideoxy chain termination method. The nucleotide sequence was then confirmed by cycle sequencing and analysed using the computer programs of RIBIODNASIS and MicroGenie which were linked to the Data Bank .